Role of Pictograms in Educating Diabetic Patients about Medication use and Life Style Modifications - Sankar, Veintramuthu; Krishna, Ramya; Reddy, Vuyyuru Krishna; Mahendiran, Narmadha Muthu; Hussain, Sameer; Parthasarathy, Rama (Indian Journal of Pharmacy Practice)
Introduction: Diabetes mellitus is a chronic disease that occurs when the pancreas is no longer able to make insulin, or when the body cannot make good use of the insulin it produces. It can be controlled using oral hypoglycaemic agents and/or insulin and lifestyle modifications. This study examines the role of pictograms in educating the diabetic patients about proper medication use and lifestyle modifications. It is an open label, observational comparative study. Objectives: To educate diabetic patients about proper medication use and lifestyle modifications using pictograms. To identify whether comprehension of pictogram differs based on gender, age group, level of education and compliance to medications in diabetic patients and to develop a leaflet containing pictograms which convey information about lifestyle modifications and medication use in diabetic patients. Method: A prospective-observational comparative study of 6 months duration was undertaken with 100 participants for Phase-1 (Survey; n=100) to select the best understood pictograms from the 24 pictograms selected. This set was carried out for Phase-2 (one-on-one interview; n=100), which had Guessability and Translucency as its components. Guessability study was carried out in 50 diabetic patients and their response to pictograms was recorded in a 3 point Likert scale. Modifications were made to the pictograms based on the difficulties faced by the patients in understanding the pictograms. These modified pictograms were used for Translucency study and result was obtained using 5 point Likert scale. We use student t-test and Chi-Square test using SPSS 19 to analyze the data. Results: The results of this study show that pictograms are generally well understood by the diabetic patients when the intended meaning of the pictograms are explained and are accompanied with text. The statistically significant p values were obtained only with levels of education in both Guessability (0.040) and Translucency (0.050). The overall Guessability (all pictograms included) was 69.6% and the overall Translucency was 90.9%. Conclusion: The result from this study suggests that pictograms play a vital role in educating patients and can be used as an effective counselling aid in a low-literacy group of people.
Keywords: Diabetes; Lifestyle modification; Guessability; Medication Use; Pictograms; Translucency